PENGARUH BRAND IMAGE, LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MIXUE (STUDI KASUS KONSUMEN MIXUE JL. JAWA JEMBER) - Ula, Nazzelia; Ashilah, Khittah; Choiriyah, Farida Umi (Fakultas Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of brand image, halal labels and prices on purchasing decisions. Brand Image is the identity of the company as a differentiator from competing companies. A halal label is a logo, writing that shows that a product is halal. Price is the sum of all the values that consumers exchange by using a good or service for various benefits. Purchasing decision is an action in analyzing their needs through the selection of a product so that there is an attraction to buy. The data source of this research uses primary and secondary data. Primary data through observation and questionnaires given directly to consumers of Mixue Jl Jawa Jember while secondary data through journals, articles and the internet. Researchers collected data by accidental sampling technique to consumers who had purchased mixue and by using the Malhotra formula distributing questionnaires to 85 respondents. This research uses multiple linear regression test. The results of the study show that partially brand image and price variables have a significant influence on purchasing decisions, while the halal label does not have a significant influence on purchasing decisions. Simultaneously brand image, halal label and price have a significant effect on purchasing decisions for Mixue Jl Jawa jember.